TAKTIK ILMU POLITIK KOMPENI BELANDA SEBAGAI USAHA MEMPENGARUHI PAKUBUWANA IV KERATON SURAKARTA PADA BABAD PAKEPUNG - Adhimas Hayyun Pradhipa; Mohamad Juniawan Saputra (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The Babad Pakepung manuscript is a manuscript that contains information about the Surakarta Palace, starting from the beginning of the leadership of Pakubuwana IV, the war at the Surakarta Palace, until the pressure of the Surakarta Palace. This article discusses the political science tactics of the Dutch Company as an attempt to influence Pakubuwana IV Keraton Surakarta in Babad Pakepung. The formulation of the problem raised is (1) What was the form of political science tactics of the Dutch Company in an effort to influence Pakubuwana IV Keraton Surakarta on Babad Pakepung? And (2) How did the Dutch Company's political science tactics influence the Surakarta Palace? Based on the problem formulation, the aim of this research is to describe the political science tactics used by the Dutch Company in influencing Pakubuwana IV who was reigning at the Surakarta Palace in the Babad Pakepung. The research method used is a descriptive qualitative method with a philological theory approach, postcolonialism theory, and Erdward Spranger's personality psychology theory. It is felt that the chosen theory makes it easier to carry out research to answer existing problems. The results of this research are that the political science tactic divide et impera has a greater influence than sending letters containing seduction. The impact was internal conflict within the Surakarta Palace because the deliberations that took place did not find a solution.